PENGARUH CITRA MEREK, GAYA HIDUP, DAN CONTENT MARKETING TERHADAP KEPUTUSAN PEMBELIAN: (Studi pada Pengguna Layanan Berlangganan Netflix di Jakarta Selatan) - Dwifani Gusma Zamroni; Kartini Istikomah (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
Netflix is a video on demand application that provides various film entertainment. The purpose of this research is to determine the influence that purchasing decisions have on brand image, lifestyle and content marketing. A quantitative approach using the population of all Netflix subscription service users in South Jakarta is. The technique used is non-probability sampling because the population size is not known with certainty. Data was collected through distributing questionnaires. The sample used in this research was 97 respondents who were determined by purposive sampling using specified criteria. Data were analyzed using SPSS version 27 software. The research results showed that purchasing decisions were significantly influenced by brand image, lifestyle, and content marketing had a significant influence on purchasing decisions.